Diplomacy's Value Creating Security in 1920s Europe and the Contemporary Middle East - Rathbun, Brian C. (Cornell University Press, 2014)
What is the value of diplomacy? How does it affect the course of foreign affairs independent of the distribution of power and foreign policy interests? Theories of international relations too often implicitly reduce the dynamics and outcomes of diplomacy to structural factors rather than the subtle qualities of negotiation. If diplomacy is an independent effect on the conduct of world politics, it has to add value, and we have to be able to show what that value is. In Diplomacy's Value, Brian C. Rathbun sets forth a comprehensive theory of diplomacy, based on his understanding that political leaders have distinct diplomatic styles-coercive bargaining, reasoned dialogue, and pragmatic statecraft.
Description based on print version record.
KU Select 2017: Backlist Collection
Keywords: Political Science / International Relations; Political science; Electronic books